Chemical Conjugation in Drug Delivery Systems - Eras, Alexis; Castillo, Danna; Suárez, Margarita; Vispo, Nelson Santiago; Albericio, Fernando; Rodriguez, Hortensia (Frontiers in Chemistry, 2022)
Cancer is one of the diseases with the highest mortality rate. Treatments to mitigate it are usually so intense and invasive that they weaken the patient to cure as dangerous as the own disease. From some time ago until today, to reduce resistance generated by the constant administration of the drug and improve its pharmacokinetics, scientists have been developing drug delivery systems (DDS’s) technology. DDS platforms aim to maximize the drugs’ effectiveness by directing them to reach the affected area by the disease and, therefore, reduce the potential side effects. Erythrocytes, antibodies, and nanoparticles have been used as carriers in this regard. Eleven Antibody Drug Conjugates (ADC’s) involving covalent linkage have been commercialized as a promising cancer treatment in the last years. This review describes the general features and applications of Drug Delivery Systems focused on the covalent conjugation system that binds the antibody carrier to the cytotoxic drug.